2020
DOI: 10.1200/go.20.00163
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study of Pediatric Early Warning Systems’ Impact on Interdisciplinary Communication in Two Pediatric Oncology Hospitals With Varying Resources

Abstract: PURPOSE Hospitalized pediatric oncology patients are at high risk of deterioration and require frequent interdisciplinary communication to deliver high-quality care. Pediatric early warning systems (PEWS) are used by hospitals to reduce deterioration, but it is unknown how these systems affect communication about patient care in high- and limited-resource pediatric oncology settings. METHODS This qualitative study included semistructured interviews describing PEWS and subsequent team communication at 2 pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 28 publications
2
36
0
4
Order By: Relevance
“…Multidisciplinary pediatric oncology clinicians were interviewed at Unidad Nacional de Oncologıá Pediatrica (UNOP) and St. Jude Children's Research Hospital (SJCRH), two free-standing pediatric oncology hospitals, between October and December 2018. Detailed methods of this study including setting, population, and data collection have been previously described (8). Briefly, UNOP is located in Guatemala City, Guatemala, an upper middle-income country with a gross national income (GNI) of US $4,410 per capita.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary pediatric oncology clinicians were interviewed at Unidad Nacional de Oncologıá Pediatrica (UNOP) and St. Jude Children's Research Hospital (SJCRH), two free-standing pediatric oncology hospitals, between October and December 2018. Detailed methods of this study including setting, population, and data collection have been previously described (8). Briefly, UNOP is located in Guatemala City, Guatemala, an upper middle-income country with a gross national income (GNI) of US $4,410 per capita.…”
Section: Methodsmentioning
confidence: 99%
“…While PEWS have been primarily implemented and studied in high-resource settings, pediatric cancer is a global health issue, with approximately 90% of pediatric cancer diagnoses occurring in countries with limited resources (7). Previous studies have shown that PEWS implementation in a resource-limited pediatric oncology setting reduces clinical deterioration events and hospital costs, while improving interdisciplinary communication (5,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Interviews were conducted during the fall of 2018 at two hospitals dedicated to the care of children with cancer: Unidad Nacional de Oncología Pediátrica (UNOP) in Guatemala City, Guatemala and St. Jude Children’s Research Hospital (St. Jude) in Memphis, USA. Study design and methods have been previously described ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transcribed interviews underwent qualitative content analysis using codes derived inductively from transcript review ( 13 ). Code definitions are described in Supplemental Table 1 ( 10 ). Each interview transcript was independently coded by two researchers (MG, DG, GF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation